Load Balancer Operation Analyses of Video-Conference Service - A. N. Markov; A. I. Paramonov (Цифровая трансформация, 2022)
The need to implement balancing of the video conferencing service (VCS) when used in educational processes is shown. The structure of building a VCS with a load balancer is considered. A computer experiment is being conducted on the VCS. Based on the results of a computer experiment, graphs were generated for the selected BigBlueButton VCS with a load balancer. The graphs of the load on the hardware components of the virtual server at three stages of testing for the central processor, RAM, and network interfaces both within the service and in the structure of the local computer network are given. The results of the analysis of graphs are described in order to identify the key features of the operation of the video conferencing service with a load balancer. The most loaded hardware components of the virtual server are determined. The problems of service operation with the chosen balancing algorithm are formulated.